Impact Of Social Media On Social Movements (Trinity Journal of Management, IT & Media (TJMITM), 2016)
With the advent of prominent social networking sites and blogs,  citizens have taken upon themselves to undo the wrongs in the  society. The SNS have given a voice to the citizens to advocate  an opinion and advance the movement- Anna Hazare Movement,  the Arab Uprising are all products of SNS influence. Like Print  Journalism is attributed to have played a significant role in the  freedom of independence, SNS can be rightly herald as the new  age medium to mobilize support for the cause and fight for their  right. Social media strengths lie in its interactive nature and the capability  to reach millions of users within short span of time. Everybody  has an opinion on SNS, it is probably one of the medium where  there is no gatekeeper filtering news on the basis of race, religion,  sex or ethnicity and if you have views voice it. Moreover, SNS is  a versatile medium where you can couple powerful words with  videos and pictures.  Earlier the Government used to be dependent on opinion polls  to gauge the mood of the public. With the introduction of social  media the dependence on media has diminished as now SNS are  the best indicator of the public atmosphere. It is not only ideal  but a necessity for politicians to be present on SNS. Barrack  Obama, the first African President of United States of America  acknowledges the contribution of Social media for his win. In  India, Narendra Modi, Prime Minister of India is called the first  Facebook Prime Minister.
Keywords: Impact Of Social Media; Social Movements; Anna Hazare Movement